Predictos of serious violent recidivism - Result from a cohort study - Martinez, R. (Journal of interpersonal violence, 1997)
Despite the growth in research on violent offenders, little is known about the existence of a career in violent crime. To fill the gap in the knowledge of violent offenders, the authors conducted a retrospective longitudinal study of all individuals arrested in Franklin County, OH, in 1973 for an FBI index violent crime. Those continuing in post-1973 criminal activities (as measured by an arrest) were not high-rate violent offenders; on the other hand, they maintained a higher than average amount of index violent and other violent criminal activity. They were arrested for a large number of serious crimes and committed a large number of the cohort's violent offenses. Contrary to expectations, many of these subjects seriously persisted in violent activities